Some Aspects of Women’s Position in the Kingdom of Yugoslavia (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
This text deals with some issues related to women’s emancipation in the Kingdom of Yugoslavia. Here we wish to present how first feminist societies were established, and what their role in the society was. We also gave an overview on the legal system and women’s position in it. The First feminist organization was established in 1919 in Belgrade, and after that in Ljubljana, Zagreb, Sarajevo. One of the main goals for Yugoslav feminists was the issue of getting suffrage for women. But these feminists did not have much success because of the many obstacles they had to face, one of them being the fact that a unique legal system had not been established in the Kingdom of Yugoslavia.
Keywords: Feminism; Women societies; emancipation; Kingdom of Yugoslavia